Kualitas Audit Syariah Dalam Meningkatkan Kinerja Keuangan Bank Umum Syariah - Nina Andriany Nasution (Jurnal Ilmiah Ekonomi Islam, 2022)
Sharia audit quality which includes Sharia Accounting Standards (SAS), Standard Operating Procedures (SOP), Internal Audit Competence and External Audit Independence can support the improvement of Islamic financial performance consisting of CAR, NPF, ROA, FDR and BOPO. This shows the continuity of sharia compliance and professionalization provided by the quality of sharia audits according to sharia accounting standards and following sharia standard operating procedures to improve the financial performance of Islamic commercial banks by assessing the profitability, liquidity and investment of Islamic commercial banks. The purpose of this study is to analyze the quality of sharia audits in improving the financial performance of Islamic commercial banks. The method used in this research is quantitative descriptive method with analysis techniques using the SEM (Structural Equation Modeling) method with secondary data sources from Islamic Banking Statistics. The results of this study indicate that there is an effect of sharia audit quality on improving the financial performance of Islamic commercial banks.